PROJECT-BASED APPROACH TO ANTI-CRISIS MANAGEMENT OF ENTERPRISES IN WARTIME - Halushko, Leonid; Androshchuk, Ilona; Muzychenko, Anatolii; Podopryhora, Artem (Social Development: Economic and Legal Issues, 2026)
The potential of project management as an effective tool for crisis management in enterprises during wartime is demonstrated in this paper. A range of general scientific methods, including analysis, synthesis, comparison, generalization, logical modelling and a systems approach, is employed in the study. The specific nature of the crisis processes caused by Russia’s full-scale military aggression against Ukraine, as well as their impact on the functioning of domestic enterprises, is analyzed. Particular attention is paid to the problems of labor force loss, the complication of logistics processes, disruptions to supply chains, energy shortages, rising costs and physical threats to the operation of enterprises. A comparative analysis of the key aspects of crisis management and project management is conducted, through which significant similarities between them are identified in such areas as timely decision-making, management of limited resources, leadership, team interaction and the adaptability of organizational structures. Based on the concept of the Project Management Triangle, a crisis is interpreted as a project that, from the outset, exceeds the permissible limits of time, cost and scope of implementation. The value of using project management tools to respond to both sudden and long-term crises is substantiated. Furthermore, the practical aspects of implementing a project-based approach to crisis management are examined using the Ukrainian company Hydrosila APM as a case study. The problems of the enterprise’s production system functioning under wartime conditions are analyzed, the objectives of the crisis management project are formulated, and a set of management decisions regarding the adaptation of the organizational structure of production, the reorganization of production units, the reconfiguration of equipment, and the more efficient use of personnel is proposed. It is demonstrated by the results of the study that the use of a comprehensive project-based approach not only allows a rapid response to crisis challenges to be ensured, but also contributes to the systematic implementation of anti-crisis measures, the optimization of the organizational structure, and the enhancement of the efficiency of enterprise resource utilization under wartime conditions.